2017
DOI: 10.1136/bmjopen-2017-016559
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cancers in Lahore, Pakistan, among children, adolescents and adults, 2010–2012: a cross-sectional study part 2

Abstract: ObjectivesTo estimate the cancer incidence by age group for the Lahore district population within the Punjab Cancer Registry (PCR), Pakistan. The average annual population of Lahore was 9.8 million in 2010–2012. This is a sequel to a study published earlier.DesignA cross-sectional study.SettingThe registry has 19 centres in Lahore reporting their data to the coordinating office located within the Shaukat Khanum Memorial Cancer Hospital and Research Center (SKMCH&RC), Lahore, Pakistan.ParticipantsData existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Research in China has shown that the majority of children with cancer are aged 0-5 years (57.14%) (Zheng et al, 2015), while results from Korea between 1999 and 2011 suggest that the highest prevalence is in children aged 10-14 years (32.20%) (Park et al, 2016). Research in Pakistan as a developing country shows that the most common age group to suffer from cancer is 5-9 years, with minimal differences between the other age groups (Badar & Mahmood, 2017). In contrast, research carried out in Thailand between 1985 and 2009 found that the age group most likely to have pediatric cancer was 0-4 years (Wiangnon, Jetsrisuparb, Komvilaisak, & Suwanrungruang, 2014), and research carried out in 1993-2012 in Northeast Thailand found the same (Wongmeerit, Suwanrungruang, Jetsrisuparb, Komvilaisak, & Wiangnon, 2016).…”
Section: Age Group Of Pediatric Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in China has shown that the majority of children with cancer are aged 0-5 years (57.14%) (Zheng et al, 2015), while results from Korea between 1999 and 2011 suggest that the highest prevalence is in children aged 10-14 years (32.20%) (Park et al, 2016). Research in Pakistan as a developing country shows that the most common age group to suffer from cancer is 5-9 years, with minimal differences between the other age groups (Badar & Mahmood, 2017). In contrast, research carried out in Thailand between 1985 and 2009 found that the age group most likely to have pediatric cancer was 0-4 years (Wiangnon, Jetsrisuparb, Komvilaisak, & Suwanrungruang, 2014), and research carried out in 1993-2012 in Northeast Thailand found the same (Wongmeerit, Suwanrungruang, Jetsrisuparb, Komvilaisak, & Wiangnon, 2016).…”
Section: Age Group Of Pediatric Cancer Patientsmentioning
confidence: 99%
“…Research in India and Pakistan has reported that leukemia is more common in male children aged 0-4 years. Indeed, leukemia is the most common childhood cancer globally, accounting for 30-50% of pediatric cancer cases in Eastern Mediterranean countries, 20-40% in the USA, and 40-50% in Europe (Asthana, Labani, Mehrana, & Bakhshi, 2018;Badar & Mahmood, 2017). The most common types of leukemia that occur in children and adolescents in the USA are ALL and Acute Myeloblastic Leukemia (AML).…”
Section: Type Of Cancer In Pediatric Cancer Patientsmentioning
confidence: 99%
“…International reports, conversely, show a nearly constant incidence of this neoplasm [3,4]. The causes of brain and central nervous system neoplasms are unknown, in addition to the heterogeneous group they represent [16,17]. Some risk factors have been described, including: exposure to radiation, chemical products, infection; a prior history of cancer, genetic conditions and family histories [5,18].…”
Section: Incidence In Young Adult Menmentioning
confidence: 99%
“…McNicol and Dodd 11 detected HPV even in prostate cancer (PC) tissues of adults. Oddly enough, PC has not been documented in very young and sexually inactive male 12 children. The mortality burden of PC has risen to over 360,000 deaths per year 13 .…”
Section: Introductionmentioning
confidence: 97%